2013
DOI: 10.1017/s1047951113001522
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of very low-dose prostaglandin E1 in duct-dependent congenital heart disease

Abstract: Our findings indicate that the infusion of prostaglandin at a very low dose (0.003-0.005 mcg/kg/minute) is sufficient to maintain the patency of the ductus arteriosus. A higher dose of prostaglandin E1 may be necessary in patients with inadequate systemic blood flow.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 18 publications
0
10
0
1
Order By: Relevance
“…Previous studies of the pharmacological activities of PGE1 mainly focused on its effect on vasodilation. These studies showed that PGE1 can increase peripheral blood flow in heart, kidney, liver, and eyes in patients with peripheral vascular disease (Shin et al, 2012; Zhao et al, 2013; Yucel et al, 2015; Steigerwalt et al, 2016; Li et al, 2018). Emerging evidence has also shown that PGE1 activates angiogenesis and fibrinolysis, inhibits platelet aggregation, fibrinogenesis, inflammatory cell activity and proliferation (Schror and Hohlfeld, 2004; Huang et al, 2008; Gao et al, 2010).…”
Section: Introductionmentioning
confidence: 97%
“…Previous studies of the pharmacological activities of PGE1 mainly focused on its effect on vasodilation. These studies showed that PGE1 can increase peripheral blood flow in heart, kidney, liver, and eyes in patients with peripheral vascular disease (Shin et al, 2012; Zhao et al, 2013; Yucel et al, 2015; Steigerwalt et al, 2016; Li et al, 2018). Emerging evidence has also shown that PGE1 activates angiogenesis and fibrinolysis, inhibits platelet aggregation, fibrinogenesis, inflammatory cell activity and proliferation (Schror and Hohlfeld, 2004; Huang et al, 2008; Gao et al, 2010).…”
Section: Introductionmentioning
confidence: 97%
“…This is in contrast with other studies that have suggested that patients with systemic obstruction require higher doses. 12,18 One possible explanation for this discrepancy is that our systemic obstruction cohort had a high level of prenatal diagnosis (74%) compared with other studies, where this patient population was typically older at diagnosis, and thus we were able to start prostaglandin E1 earlier in patients with systemic obstruction. Within our study, higher doses were required for those with systemic obstruction who were diagnosed postnatally (5/23, 22%) than for those diagnosed prenatally (4/65, 6%, p = 0.049).…”
Section: Efficacy Of Low-dose Prostaglandin E1mentioning
confidence: 82%
“…The authors also concluded that lesions with systemic obstruction may require higher doses. 18 Despite these investigations into the efficacy of lower dose prostaglandin E1, many dosage guidelines continue to recommend high starting doses. [6][7][8] Our current study is the largest retrospective study in the current era and is unique in describing infants who were uniformly started on low-dose prostaglandin E1, even prior to transport, and utilised the same low-dose infusion for maintenance.…”
Section: Efficacy Of Low-dose Prostaglandin E1mentioning
confidence: 99%
See 1 more Smart Citation
“…Prostaglandin E1 (PGE 1 ) kann eingesetzt werden, wenn sich der Ductus arteriosus schließt, um ein Rechtsherzversagen bei schwer betroffenen NG zu verhindern. PGE 1 verhindert den Verschluss des Ductus arteriosus und schafft so ein "Überdruckventil" und druckentlastet so das rechte Herz auf Kosten einer verstärkten Hypoxämie (18). Dieser Therapieansatz ist bislang nicht evidenzbasiert und daher als individueller Heilversuch zu betrachten.…”
Section: Prostaglandin E1unclassified